Application of mesenchymal stem cells for treating spinal cord injury in dogs: Mechanisms and their therapeutic efficacy - MILI, BHABESH; BURAGOHAIN, LUKUMONI; RALTE, LALCHAWIMAWIA; CHUTIA, TUKHESWAR; GOGOI, AMRIT; BARMAN, UTPAL (The Indian Journal of Animal Sciences, 2022)
Despite progress in the treatment of spinal cord injury (SCI), recovery of the spinal cord with normal motor andsensory activities remains a challenge due to the complex anatomy of the spine, and its limited regeneration potential in mammals. Recently, the clinical application of mesenchymal stem cells (MSCs) in SCI led to promising results in both human and veterinary medicine. The mechanism by which MSCs might promote wound healing of SCI has been extensively investigated. Previous reports have suggested that transplanted MSCs enhance the numbers of neurons and glial cells, prevent neuronal apoptosis, inhibit inflammation, stimulate vascular angiogenesis, axonal myelination, and neuro-regeneration at the lesion site. It has also been reported that therapeutic applicability depends on the source of derivation of MSCs and their differentiation capability into specific cell lineages at the transplanted site. Therefore, this review is focussed on precise mechanisms by which transplantation of MSCs promote functional recovery and also addresses the challenges to improve the therapeutic efficacy of MSCs for treating SCI in dogs.